Kepuasan Kerja sebagai Mediator Kecerdasan Emosional dan Kinerja Karyawan di Puskesmas Pontianak - Rika, Septiani; Hendri, Muhammad Irfani; Mufrihah, Mazayatul; Daud, Ilzar; Marumpe, Dody Pratama (Lembaga Publikasi Ilmiah Nusantara, 2025)
Employee performance at Pontianak City's public health center (Puskesmas) has recently revealed a gap between the goals outlined in the Health Department's Performance Agreement and actual results. Emotional intelligence is one of the internal characteristics that may impact performance, as indicated by this condition. Results from earlier research on the connection between employee performance and emotional intelligence have been mixed. Furthermore, only a small number of studies—especially in Pontianak City—have positioned job satisfaction as a mediating variable in the context of basic healthcare services. This study uses job satisfaction as a mediating variable to examine how emotional intelligence affects Puskesmas employees' performance in Pontianak City. 225 Puskesmas employees who were chosen through purposive sampling were given questionnaires as part of a quantitative approach. Using the SmartPLS software, structural equation modeling, or SEM, was used to analyze the data. The findings demonstrate that emotional intelligence significantly and favorably affects employee performance as well as job satisfaction. Additionally, it was discovered that a significant mediating variable in the association between performance and emotional intelligence was job satisfaction. These results emphasize how crucial it is to enhance job pleasure and cultivate emotional intelligence as calculated measures to boost worker performance. The practical implication is that in order to improve the quality of public health services in a sustainable manner, Puskesmas management and the Health Department should focus more on the psychological aspects of their workforce.